Otimização das propriedades luminescentes do LiAl5O8 dopado com európio - Silva, Ariosvaldo Junior Sousa (2022)
The present study evidences the production, structural and optical characterization of lithium aluminate (LiAl5O8) pure and doped with different concentrations of europium, which were produced by the modified sol-gel method, using D-(+)-glucose anhydrous as a chelating agent. Structural analysis was performed using X-ray diffraction (XRD) and X-ray absorption spectroscopy (XAS). The XRD results show the formation of the desired crystalline phase, in accordance with the crystallographic pattern defined by the P4332 refinement Rietveld graph Williamson-Hall, it is verified that all samples produced have an estimated crystallite in the nanometric order around 13-69 nm. Also based on the diffractograms, the solubility limit of LiAl5O8 in relation to the europium dopant was established. The XAS spectra indicate that europium, when introduced into lithium aluminate, is in the trivalent oxidation state (Eu3+), however, there are small traces of europium in its divalent state (Eu2+). Furthermore, by analyzing and processing the XAS spectra by the Demeter, it was possible to extract information regarding the chemical environment of the dopant ion, such as the interatomic distances between neighboring ions, disorder factor and their respective symmetries. The optical aspects were investigated by means of photoluminescence (PL) and X-ray excited optical luminescence (XEOL) spectroscopy. The PL results confirmed the effectiveness of the LiAl5O8, in which all spectra express the typical transitions of Eu3+ in which the 5D0→7F2 (620 nm) has the highest luminescent intensity, when sensitized at 395 nm and 275 nm. The same was observed for the XEOL spectra when excited at 6982 eV, which in addition to the Eu3+ also exhibit the typical Eu2+. Furthermore, the PL and XEOL signals exhibit quenching for the same europium concentration value, which coincides with the observed value for the solubility limit indicated in the XRD (3 %). However, the PL and XEOL signals reveal the existence of iron and chromium contaminants, which have a noticeable emission in the photoluminescent region of Eu3+. However, this characteristic does not influence the predicted integral emission color for Eu3+ in the red region, as shown in the chromaticity diagram. It was also found that the doped samples have an emission lifetime in the order of milliseconds. Therefore, it is feasible to assume, based on the results obtained, an estimate of the maximum concentration limit of the europium dopant in LiAl5O8, guaranteeing its reproducibility and greater luminescent emission PL and XEOL, suggesting a possible application in diodes (LED).